Adding salt to foods and risk of incident depression and anxiety - Weiwei Wang; Xiaotian Chang; Feifei Lin; Lei Feng; Mengying Wang; Jie Huang; Tao Wu (BMC Medicine)
Abstract Background Diet is a well-known determinant of mental health outcomes. However, epidemiologic evidence on salt consumption with the risk of developing depression and anxiety is still very limited. This study aimed to examine the association between adding salt to foods and incident depression and anxiety longitudinally. Methods This study used data from 444,787 adults who had never been diagnosed with depression or anxiety at baseline from the UK Biobank, a national community-based cohort from 2006 to 2010. Adding salt to foods was measured using a four-point Likert scale at baseline from a touch-screen questionnaire. The outcomes were incidents of diagnosed depression (F32-F33) and anxiety (F40-F48), defined by the International Statistical Classification of Diseases and Related Health Problems, 10th Revision codes. Cox proportional hazards models were used to investigate the association between the frequency of adding salt to foods and incident depression and anxiety. Results During a mean follow-up period of 14.5 years, 16,319 incidents of depression and 18,959 incidents of anxiety were documented. A higher frequency of adding salt to foods was associated with elevated risk for depression and anxiety. Compared with the group of never/rarely adding salt to foods, the adjusted HRs of incident depression were 1.07 (95% CI: 1.02–1.12), 1.18 (95% CI: 1.10–1.26), and 1.29 (95% CI: 1.18–1.41) across the groups of sometimes, usually, and always, respectively (P trend < 0.001). Participants who reported always adding salt to foods had a 1.17-fold higher risk for developing anxiety (95% CI: 1.07–1.28) compared with those who never/rarely added salt to foods. Conclusions A higher frequency of adding salt to foods was independently associated with a higher hazard of depression and anxiety. Interventions such as public awareness campaigns promoting reduced salt consumption may be promising preventative measures to reduce the incidence of depression and anxiety.